Osmotic Adjustment of Cultured Tobacco Cells (Nicotiana tabacum var. Samsum) Grown on Sodium Chloride - Heyser, James W. (1981)
Tobacco cell cultures (var. Samsum) were grown on increasing levels of NaCl to select variants for increased salt tolerance. The osmotic adjustment of NaCl-adapted and nonadapted cell lines was studied. Both cell lines were grown on modified Linsmaier and Skoog medium with or without NaCl. Few differences were found in the response of adapted and nonadapted lines to NaCl. The concentrations of sugars, Na(+), Cl(−), and NO(3)(−) were identical in the cells and medium. Potassium and amino acids were accumulated by the cells. All of the above solutes accounted for 80 to 90% of the osmotic potential for both cell lines when grown on basal medium with or without NaCl. The osmotic potential of growing cells was always 1 to 3 bars more negative than that of the medium. During the first 10 days culture, the cells hydrolyzed the 117 millimolar sucrose present in the fresh media, and the media became more negative by 3 bars. Growing cells absorbed and metabolized the sugars, NH(4)(+), and NO(3)(−) during the next 25 days, and the osmotic potential of the media and cells became less negative. The addition of 130 millimolar NaCl made the media and cells osmotically more negative by 6 bars throughout the growth cycle, as compared with cells growing on basal medium. The efflux of cellular solutes during distilled H(2)O washes was resolved into two components. The fast component (0.6 to 1.7 minutes half-time) included solutes of the free space and cytoplasm, whereas the slow component (1.6 to 4.9 hours half-time) represented the vacuolar solutes. Sodium and Cl(−) were present in the vacuole. No differences were observed in the solute efflux between the adapted and nonadapted cell lines.